2020
DOI: 10.3390/transplantology1010003
|View full text |Cite
|
Sign up to set email alerts
|

Non-HLA Abs in Solid Organ Transplantation

Abstract: The role of anti-HLA antibodies in solid organ rejection is well established and these antibodies are routinely monitored both in patients in the waiting list and in the post-transplant setting. More recently, the presence of other antibodies directed towards non-HLA antigens, or the so-called minor histocompatibility antigens, has drawn the attention of the transplant community; however, their possible involvement in the graft outcome remains uncertain. These antibodies have been described to possibly have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, several studies have examined the importance of anti-MICA antibodies in KT and have shown that pre-transplant or post-transplant antibodies can be associated with the development of ABMR or TCMR and that they negatively impact kidney graft function [ 60 , 61 , 62 , 63 , 64 ]. The prevalence of anti-MICA antibodies in KT can be as high as 20% [ 65 ]. Preformed anti-MICA antibodies could be formed by classic sensitizing events such as pregnancy, blood transfusions and previous transplants [ 66 ].…”
Section: Types Of Non-hla Ab In Kidney Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, several studies have examined the importance of anti-MICA antibodies in KT and have shown that pre-transplant or post-transplant antibodies can be associated with the development of ABMR or TCMR and that they negatively impact kidney graft function [ 60 , 61 , 62 , 63 , 64 ]. The prevalence of anti-MICA antibodies in KT can be as high as 20% [ 65 ]. Preformed anti-MICA antibodies could be formed by classic sensitizing events such as pregnancy, blood transfusions and previous transplants [ 66 ].…”
Section: Types Of Non-hla Ab In Kidney Transplantationmentioning
confidence: 99%
“…From a clinical perspective, the incorporation of non-HLA antibodies into the immunological risk assessment could bring important benefits in the management of rejection cases. Although there are numerous studies, especially on anti-AT1R antibodies, that have demonstrated the role of non-HLA antibodies in rejection and the impact on kidney graft survival and function, there are still no recommendations and algorithms for risk assessment mediated by these antibodies in clinical practice [ 10 , 65 ]. Currently, the therapeutic approach of non-HLA antibody-mediated graft injury is based on the evidence from observational studies and case reports and consist of several solitary or combination regimens of plasma therapy, intravenous immunoglobulins, corticosteroids, antithymocyte globulin, rituximab, eculizumab, bortezomib and AT1R blockers [ 103 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Kidney transplant recipients may carry non-HLA antibodies that could produce an immune response against cells in the microcirculation of the transplanted kidney, initiating an inflammatory process which may result in antibody-mediated allograft rejection [ 11 , 12 ]. The targets for these non-HLA antibodies are often cryptic and may also be subject to regional variation because of the genetic distribution across the local population and environmental factors [ 13 ].…”
Section: Introductionmentioning
confidence: 99%